Analisis Pengaruh Motivasi Kerja dan Kemampuan Kerja Terhadap Kinerja Karyawan PT. Baris Jaya Perkasa - Lesmana, Angga; Roswaty, Roswaty; Wulandari, Try (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the effect of work motivation and work ability on employee performance at PT Baris Jaya Perkasa. The population and sample in this study were 40 employees of PT Baris Jaya Perkasa. The analysis techniques used are the classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, hypothesis test, correlation coefficient test, and coefficient of determination test which were processed using the help of the Static Product and Service Solution (SPSS) version 29 program. The results of this research are t count 4,257 > t table 2,026 on Variable X1, namely work motivation and t count 10,221 > t table 2,026 on Variable X2, namely Work Ability. In the correlation coefficient test method for the Work Motivation Variable (X1), the value is 0,568, which means that the level of relationship between work motivation and employee performance is at a moderate level. Based on the results of calculating the Coefficient of Determination (R2), it can be concluded that the percentage influence of the Work Motivation (X1) and Work Ability (X2) variables on employee performance (Y) is 0,758 or the remaining 75,8% is influenced by other variables.